SISTEM KEBIJAKAN OBJEK VITAL PT BANK RAKYAT INDONESIA (Persero) Tbk. - Edy Soesanto; Vina Damayanti; Harfanly Bramley; Indra Samuel (Cross-border, 2023)
Security management is very important in every company, especially in the banking industry. All branches of Bank BRI have increased the level of security, such as the number of police officers conducting patrols and installing CCTV as evidence when there are criminal matters that occur within Bank BRI. At Bank BRI Pujon branch, routine patrols have also been carried out to minimize loopholes for criminal acts. Security management is designed to prevent unwanted things from happening within the company that cause insecurity and discomfort in PT. Bank Rakyat Indonesia engaged in Indonesian banking institutions.